Vacancy engineering of group VI anions in NiCo2A4 (A = O, S, Se) for efficient hydrogen production by weakening the shackles of hydronium ion. (10th February 2020) - Zong, Wei; Lian, Ruqian; He, Guanjie; Guo, Hele; Ouyang, Yue; Wang, Jing; Lai, Feili; Miao, Yue-E.; Rao, Dewei; Brett, Dan; Liu, Tianxi
Abstract: Hydrogen evolution reaction (HER) has been severely suppressed by the first proton adsorption step, due to the "shackles" of the surrounding water in the form of hydronium ions (H13 O6 + ). Here, it has been found anionic vacancies in NiCo2 A4 (A = O, S, Se) can weaken the shackles of surrounding water in H13 O6 +, resulting into efficient capture of H + to form a H + -enriched field. Taking selenium vacancy-rich NiCo2 Se4 nanowires on nitrogen-doped carbon nanofibers as an example, it displays higher electrocatalytic activities with low overpotential of 168 mV at 10 mA cm −2 and a Tafel slope of 49.8 mV dec −1 . The HER performance is strongly related to the anionic vacancy size, the larger the anionic vacancy size is (VSe > VS > VO ), the higher the HER activity does. Guided by density functional theory calculations, it is found that the point defect structures can not only strengthen its interfacial linkage force with H + by weakening the hydration force of contiguous hydronium ion, but also increase its charge density for efficient electron transfer to adsorbed H + . Therefore, this work creates a useful strategy to optimize the HER performance of traditional bimetallic compounds by engineering the solid-liquid-gas three-phase interfacial interaction. Graphical abstract: Anionic vacancy is well designed in NiCo2 A4 (A = O, S, Se) to weaken the shackles of hydronium ions for efficient hydrogen production. The as-obtained VSe –NiCo2 Se4 -NWs/NCNFs electrocatalyst shows an optimized overpotential of 168 mV at 10 mA cm −2, a low Tafel slope of 49.8 mV dec −1, and excellent long-term durability in acid media. The HER performance is strongly related to the anionic vacancy size, the larger the anionic vacancy size is (VSe > VS > VO ), the higher the HER activity would be. Image 1 Highlights: A series of VA -NiCo2 A4 -NWs/NCNFs (A = O, S, Se) were prepared by facile hydrothermal and controlled annealing steps. The VA -NiCo2 A4 -NWs/NCNFs (A = O, S, Se) display higher catalytic activities than those counterpart vacancy-free samples. The electrocatalytic performance enhances with the increase of anion vacancy size. The VSe –NiCo2 Se4 -NWs/NCNFs shows an optimized overpotential of 168 mV and a low Tafel slope of 49.8 mV dec −1 .